2016
DOI: 10.1007/s12010-016-2030-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medium pH on Rhodosporidium toruloides NCYC 921 Carotenoid and Lipid Production Evaluated by Flow Cytometry

Abstract: The effect of the culture medium pH (3.5-6.0) on the carotenoid and lipid (as fatty acids) production by the yeast Rhodosporidium toruloides NCYC 921 was studied. Flow cytometry was used to evaluate the yeast's physiological response to different culture medium pH values. The yeast biomass concentration and lipid content were maxima at pH 4.0 (5.90 g/L and 21.85 % w/w, respectively), while the maximum carotenoid content (63.37 μg/g) was obtained at pH 5.0. At the exponential phase, the yeast cell size and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In particular, red yeasts of the genera Phaffia, Rhodotorula and Sporidibolus exhibit production of considerable amounts of carotenoids (Davoli et al, 2004;Dias et al, 2016), rendering these yeast strains potential sources for industrial pigment production (Freitas et al, 2014;Yen and Chang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, red yeasts of the genera Phaffia, Rhodotorula and Sporidibolus exhibit production of considerable amounts of carotenoids (Davoli et al, 2004;Dias et al, 2016), rendering these yeast strains potential sources for industrial pigment production (Freitas et al, 2014;Yen and Chang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoid production in yeast has been shown to depend on cultivation conditions (Dias, Silva, Freitas, Reis, & da Silva, ; Singh et al, ) with yields of 0.28 mg/g having been achieved in fed‐batch cultivation of R. toruloides (Dias, Sousa, Caldeira, Reis, & Lopes da Silva, ). R. toruloides produces a number of carotenoids including torularhodin, torulene, γ‐carotene, and β‐carotene.…”
Section: Resultsmentioning
confidence: 99%
“…Results in Figure3a indicated that the highest lipid content (61.5%) and dry biomass (5.2 gl -1 ) were observed at pH 5, while lipid content was gradually decreasedat pH lower or higher than 5. Dias et al (2016) reported that the Rhodosporidium toruloides NCYC 921 highest biomass and lipid content were 5.90 gl -1 and 21.85%, w/w, respectively, at pH 4.0. El-Fadaly et al (2009) considered the highest production of lipidby Cryptococcus curvatus NRRLY-1511 strain at pH 5.5.…”
Section: Effect Of Different Phmentioning
confidence: 98%